Investigating students’ use of online annotation tool in an online reading environment - Nor Fariza Mohd Nor,; Hazita Azman,; Afendi Hamat, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Studies on the use of technology as a learning tool to improve student learning and educational outcomes have been considerably reported. It is believed that technologies can be used to effectively promote learning and support learner-centred approaches. The present study describes how students used an online annotation tool to help them interact more effectively with the assigned online reading materials. The study presents findings based on the students’ usage of the Annotation tool; a type of technological tool which is designed to facilitate textual annotations and information sharing among the students when they read the assigned online materials The students are first year students who are enrolled for a compulsory subject in the English language Studies bachelor degree program. The students reported that they have difficulty understanding the new theories, concepts and terms taught in the course. Therefore, an online reading system, which integrates an online Annotation tool was designed to help students read the online materials. Data obtained from the survey questionnaire, which were distributed to 81 students and focus group interviews with 14 students revealed that the students managed to use the Annotation tool to process and comprehend the online reading texts in a more structured and systematic manner, compared to writing off line notes on the reading materials. They were also able to share their online notes and discuss the online reading materials with their friends and lecturers The results suggests that the employment of Annotation tool in a guided and structured way assist the students in their interactions with online reading materials.